Pengaruh Kinerja Keuangan, Ukuran Perusahaan, Pengungkapan Corporate Social Responsibility (CSR) Terhadap Harga Saham (Global Journal of Management and Business Research, 2019)
The purpose of this research to examine the effect of Financial Performance which is measured by using Earning per Share, Net Profit Margin, Retun On Equity, Firm Size which is measured by Total Revenue, Total Asset,, and Corporate Social Responsibility Disclosure which is measured by Economic Aspects, Environmental Aspects, Social Aspect to the Extend of stock price on food and beverage sector companies in Indonesia Stock Exchange. The stock price data was used the stock price determined by the closing price.The sample collection method has been done by using purposive sampling method and eleven of eighteen companies, which are listed in Indonesia Stock Exchange in the years of 20013-2017, are used as the research samples. The method used in this study was Structural Equation Modeling Partial Least Square (SEM-PLS). The result of the research shows that the variable Financial Performance was significantly influenced stock price. variable Firms Size was significantly influenced stock price, and variable Corporate Social Responsibility Disclosure was significantly influenced stock price.
Keywords: financial performance (EPS; NPM; ROE); firm size; corporate social responsibility disclosure; stock price